2015
DOI: 10.1186/s12904-015-0037-8
|View full text |Cite
|
Sign up to set email alerts
|

Design of, and enrollment in, the palliative care communication research initiative: a direct-observation cohort study

Abstract: BackgroundUnderstanding the characteristics of communication that foster patient-centered outcomes amid serious illness are essential for the science of palliative care. However, epidemiological cohort studies that directly observe clinical conversations can be challenging to conduct in the natural setting. We describe the successful enrollment, observation and data collection methods of the ongoing Palliative Care Communication Research Initiative (PCCRI).MethodsThe PCCRI is a multi-site cohort study of natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 68 publications
0
28
0
2
Order By: Relevance
“…(1,2) Providers and researchers often characterize conversations with patients with advanced cancer (a prototypical serious illness) in terms of “breaking bad news” or “discussing transitions of care.”(36) In the setting of serious illness among adults, special emphasis has been placed on providing realistic prognoses(7) and appraising and improving communication regarding advance care planning. (8,9) While these efforts are vitally important, the scope of communication in serious illness extends beyond planning for end-of-life care.…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) Providers and researchers often characterize conversations with patients with advanced cancer (a prototypical serious illness) in terms of “breaking bad news” or “discussing transitions of care.”(36) In the setting of serious illness among adults, special emphasis has been placed on providing realistic prognoses(7) and appraising and improving communication regarding advance care planning. (8,9) While these efforts are vitally important, the scope of communication in serious illness extends beyond planning for end-of-life care.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it should be emphasized that the communication between caregivers and the team is invaluable, as each caregiver and patient are unique and their needs must be met in the most adequate and objective way possible. 10 However, the palliative care team's role is to make them understand the purpose of such care, valuing world social questions present in the life of family members who care for a sick member in palliative care, apart from the meaning that they attribute to this experience and their actions or interactions. This is because it is possible to seek more authentic care through the understanding of this health care model.…”
Section: Family Members/caregivers' Understanding Of Palliative Carementioning
confidence: 99%
“…Care centered on patients considers the fact that the experience of a disease must be shared with and founded upon the clinical perspective. 10,16 These programs essentially aim to offer an integrated and multi-disciplinary approach to prevent and alleviate pain, suffering and other physical, psychosocial and spiritual problems associated with the disease. Palliative care is part of a philosophy that promotes life and deals with death as a natural process, without influence of its time of occurrence; support systems are available for patients to live as actively as possible until their death and for families to cope with the disease of this patient and their own mourning.…”
Section: Palliative Care Team: Support For the Family Member/caregivermentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated patient self‐ratings of optimism prior to the initial palliative care consultation, clinician estimates of survival prognosis following the consultation, and 6 months of mortality follow‐up. Details of the Palliative Care Communication Research Initiative (PCCRI) are reported elsewhere …”
Section: Methodsmentioning
confidence: 99%